Texture Discrimination Analysis between Tumour and Healthy Brain Tissue Using MaZda Program - Saleh, A Z; Lerski, R A (Al-Nahrain Journal of Science, 2018)
Four MRI images were taken from patients with proven brain tumour. Images were analysed for texture discrimination using the MaZda program. The aim of the analysis was to discriminate between the tumour tissue and the healthy tissue counterpart for each patient. Three regions of interest were taken for the tumour and another three were taken for healthy tissue. Results of these analyses have shown a significant difference between the two tissues, it has given Fisher coefficients between (138.5 and 547.5) and very low p value much lower than 0.01. It is thought to be that the effect may be mainly attributed to the possible necrotic tissue as well as the bulk of cells in the tumour which may have altered the blood perfusion influencing the MR signal.